2021
DOI: 10.1098/rspb.2021.0256
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary loss of a signalling colour is linked to increased response to conspecific chemicals

Abstract: Behavioural responses to communicative signals combine input from multiple sensory modalities and signal compensation theory predicts that evolutionary shifts in one sensory modality could impact the response to signals in other sensory modalities. Here, we conducted two types of field experiments with 11 species spread across the lizard genus Sceloporus to test the hypothesis that the loss of visual signal elements affects behavioural responses to a chemical signal (conspecific scents)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…Specifically, AVT had no impact on the motivation to perform the first visual display in untreated responders, while AVT altered the relationship between the latency to perform a tongue flick and DA concentrations in the FB. Trade-offs between visual and chemical communication occur over evolutionary time scales [Romero-Diaz et al, 2021], and plasticity in the behavioral responses of receivers may help maintain complex and multimodal signals [Martins et al, 2018]. We found that at lower DA concentrations (<0.02), AVT responders were faster to perform a tongue flick than SAL responders, but at higher DA concentrations (>0.02), SAL lizards were faster to perform a tongue flick.…”
Section: Discussionmentioning
confidence: 74%
“…Specifically, AVT had no impact on the motivation to perform the first visual display in untreated responders, while AVT altered the relationship between the latency to perform a tongue flick and DA concentrations in the FB. Trade-offs between visual and chemical communication occur over evolutionary time scales [Romero-Diaz et al, 2021], and plasticity in the behavioral responses of receivers may help maintain complex and multimodal signals [Martins et al, 2018]. We found that at lower DA concentrations (<0.02), AVT responders were faster to perform a tongue flick than SAL responders, but at higher DA concentrations (>0.02), SAL lizards were faster to perform a tongue flick.…”
Section: Discussionmentioning
confidence: 74%
“…data) and male S . jarrovii significantly increase the frequency of territorial patrolling and aggressive displays within seconds to minutes following a staged territorial intrusion by a live conspecific male 29–31 . Similarly, femoral gland secretions from male conspecifics elicit increased chemosensory behavior in S .…”
Section: Methodsmentioning
confidence: 91%
“…However, visual stimuli elicit increased frequency ofpush-up displays while scents preferentially trigger a chemosensory response. 29,31,32,54 Visual-encounter territory intrusions may represent a more immediate threat to male residents and more frequently result in a quick escalation of aggressive displays leading to physical combat. 17,55 In contrast, scent marks deposited in the substrate may be detected long after the intruder has left the territory 56,57 and elicit comparatively tamer responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations